A numerical investigation of Reynolds number sensitivity of flow characteristics around a twin-box girder. Issue 172 (January 2018) - Laima, Shujin; Jiang, Chao; Li, Hui; Chen, Wenli; Ou, Jinping
Abstract: A numerical investigation of Reynolds number sensitivity on flow past a twin-box girder was performed using large eddy simulation (LES) with Reynolds numbers of 1e2 ≤ Re ≤ 1e7. The simulation results reveal that the flow characteristics around the twin-box girder show different Reynolds number sensitivity according to the flow region and the flow state. At the leading edge, the flow experiences laminar separation-laminar reattachment state (1.5e3 < Re < 6e3), laminar separation-turbulence reattachment state (6e3 ≤ Re ≤ 8e4), and turbulence separation-turbulence reattachment flow state (Re > 8e4). Around the gap, four models exist depending on Reynolds number: laminar closed cavity flow (Re < 1.6e3), laminar open cavity flow (1.6e3 ≤ Re < 5e3), wake model (5e3 ≤ Re ≤ 9e3), and turbulent open cavity flow (Re > 8e3). In the tail of the box girder, a regular Karman vortex is first generated, and then the lower shear layer transits to turbulence, resulting in the generation of separation bubbles at the lower and upper trailing edges. However, due to the upper trailing edge being blunter than lower trailing edge, the Reynolds number sensitive range of upper trailing edge (1e2-1e7) is much wider than lower trailing edge (1e2-2e4). Highlights: Reynolds number sensitivity of flow characteristics around a twin-box girder is investigated using LES. Flow characteristics around a twin-box girder show different Re sensitivity according to the flow region and state. At leading edge, there are three types of separation-reattachment flow state depending on Reynolds number. For the blunter trailing edge, the Reynolds number sensitive range is wider.